Analysis of Factors Causing Professional Ethics Violations among Civil Servants (ASN): A Systematic Literature Review (SLR) Approach - Nst, Dito Aditia Darma; Renaldi Panjaitan; Dinar Rizki; Muhammad Arifin Harahap; Mahza Sitorus; Ika Agustina Siahaan; Khairunnisa (Journal of Scientific Insights, 2026)
This study aims to analyze the factors causing professional ethics violations among Civil Servants (ASN) through a Systematic Literature Review (SLR) approach. A total of 27 articles published between 2020 and 2025 were reviewed from Google Scholar, Scopus, DOAJ, and Sinta databases. The thematic synthesis revealed four main factors contributing to ethical violations: weak individual moral awareness, permissive organizational culture, weak supervision systems, and socio-political pressures. This analysis integrates the Theory of Planned Behavior, Virtue Ethics, and Agency Theory to explain the roots of unethical behavior among civil servants from both individual and structural perspectives. Theoretically, this study maps the dynamics of ethical behavior among civil servants, while practically offering recommendations for strengthening ethical leadership, integrity training, and value-based internal control systems. The findings emphasize the importance of professional ethics as the foundation of an integrity-driven and accountable public bureaucracy.